PCR-BASED DETECTION OF PSEUDOMONAS FLUORESCENS IN COWS AND BUFFALOES RAW MILK - Adnan M. Al –Rodhan; Hiba A . Nasear (Basrah Journal of Veterinary Research)
Investigations of the Psuedomonas fluorescens proteolysis activity is the basalobjective of this study. To achieve this objective 16S rDNA and SM2F/SM3R primerswere used in the amplification of DNA extracted from raw milk bacterial isolates. Inthe present study the 92 bacterial isolates , consisted of 42( cow raw milk isolates) and50 (buffalo raw milk isolates) obtained from 240 cows and buffaloes raw milksamples (120) for each , were subjected to phenotypic and molecular identification.The results of phenotypic identification revealed that higher ratio (41.7 and42%) forbacterial isolates plating inoculation and biochemical tests based identificationrespectively was observed in buffaloes raw milk compare to the ratio observed incows milk bacterial isolates (35 and 33.3% respectively), however the differences.between cows and buffaloes raw milk in concern to bacterial identification resultsconsidered to be not statistically significant ( P>0.05).The 16SrDNA and SM2F/SM3R based PCR results, revealed that the effect ofbreed(cow only) and age on the amplification results of the 16SrDNA andSM2F/SM3R gene product of P. fluorescens in cows and buffaloes raw milk isconsidered to be not statistically significant ( P>0.05). Depending on 16SrDNA basedPCR results higher ratio of P. fluorescens identification (62.5 %) was observed in thenative cows raw milk compare to crossbreed raw milk bacterial isolates ratio (57.7%). SM2F/SM3R based PCR results showed 33.3 and 34% of raw milk P. fluorescensisolates of cows and buffaloes respectively had protease activity